INTERFACE DE ANÁLISE DA INTERCONEXÃO EM UMA LAN USANDO CORBA - MONTEIRO, Milson Silva (2002)
This works concern software development (graphical user interface) that makes possible to analyze the interconnection in a LAN (Local Area Network) using CORBA (Common Object Request Broker Architecture) on distributed and heterogeneous environment among several outlying machines. This works presents paradigms of graphs theory: shortest paths problems (Dijkstra-Ford-Moore-Belman), maximum flow problems (Edmonds-Karp) and minimum cost flow problems (Busacker-Gowen) to formalize the interface development. We discoursed on the graphs theory and networks flows that are essentials to guarantee theoretical insight.